2022
DOI: 10.5505/pajes.2021.83548
|View full text |Cite
|
Sign up to set email alerts
|

A statistical evaluation of the effect of natural gas usage for urban heating on the air quality of Erzurum City via SO2 ve PM10

Abstract: Bu çalışmada Erzurum kent atmosferindeki hava kalitesinin değişimi; Erzurum'da hava kirliliğinin ilk kez görülmeye başlandığı 1978-1979 kış döneminden başlayarak 2018-2019 dönemine kadar kükürt dioksit (SO2) ve çapı 10 mikrondan küçük partikül madde (PM10) parametreleri kriter olarak alınmış; kent atmosferindeki nispi nem, ortalama sıcaklık, yağış, rüzgâr yönü ve hızı gibi meteorolojik parametreler de göz önünde bulundurularak istatistiksel olarak incelenmiştir. Bu amaçla görünürde ilişkisiz regresyon modeller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In addition, studies conducted in the provinces of Kütahya, Erzurum, Batman and Isparta in our country have concluded that the effect of fuels used for heating housing on air pollution is high [12][13]. In a study conducted in Erzurum, it was emphasized that with the widespread use of natural gas for heating purposes in the city, the PM10 concentration decreased compared to the period before the use of natural gas [25]. In a study conducted in China, it was reported that PM10 concentration is mainly contributed from domestic heating [26].…”
Section: The Relationship Between Fuel Use and Air Pollution In Resid...mentioning
confidence: 99%
“…In addition, studies conducted in the provinces of Kütahya, Erzurum, Batman and Isparta in our country have concluded that the effect of fuels used for heating housing on air pollution is high [12][13]. In a study conducted in Erzurum, it was emphasized that with the widespread use of natural gas for heating purposes in the city, the PM10 concentration decreased compared to the period before the use of natural gas [25]. In a study conducted in China, it was reported that PM10 concentration is mainly contributed from domestic heating [26].…”
Section: The Relationship Between Fuel Use and Air Pollution In Resid...mentioning
confidence: 99%